Preparation method of palm oil-based ionic conductive elastomer

By using palm oil-based eutectic solvents and graphene oxide reinforced materials, palm oil-based ionic conductive elastomers with high conductivity and toughness are prepared, which solves the problems of insufficient competitiveness and poor conductivity of petroleum-based materials in the prior art, and realizes the preparation of materials suitable for high-performance flexible pressure sensors.

CN119505085AActive Publication Date: 2025-02-25VIGIT NEW MATERIAL TECHNOLOGY (TAIZHOU) CO LTD

Patent Information

Application Number
CN202411689926.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2025-02-25
Estimated Expiration
2044-11-25

AI Technical Summary

Technical Problem

The petroleum-based materials used in existing photocuring 3D printing limit their market competitiveness, and the electrical conductivity of palm oil-based ionic conductive elastomers is not excellent, making them difficult to apply to high-performance sensors.

Method used

Palm oil-based ionic conductive elastomer is prepared by photocuring 3D printing technology to construct an ordered microstructure to improve conductivity and compression sensitivity coefficient.

Benefits of technology

It improves the conductivity and toughness of palm oil-based ionic conductive elastomers, enhances its application potential in flexible pressure sensors, and solves the problem of low sensitivity coefficient of traditional pressure sensors.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119505085A_ABST
    Figure CN119505085A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of a palm oil-based ionic conductive elastomer, and belongs to the field of bio-based elastomers. Palm oil fatty acid acrylamide ethyl ester is used as a raw material, a novel green deep-eutectic solvent is used as a reactive solvent, and the palm oil fatty acid acrylamide ethyl ester and the novel green deep-eutectic solvent are blended to prepare the palm oil-based ionic conductive elastomer under the action of a photoinitiator through a photocuring 3D printing technology. On the basis of the system, a small amount of graphene oxide is added, and the graphene oxide enhanced palm oil-based ionic conductive elastomer is prepared by adopting a 3D printing technology. The palm oil-based ionic conductive elastomer prepared by the invention has very high tensile elongation at break, excellent toughness, good conductivity, high printing precision and wide application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of bio-based elastomers, and in particular to a preparation method of a palm oil-based ion conductive elastomer. Background Art

[0002] Photocuring 3D printing is a high-speed additive manufacturing technology that can cross-link photosensitive resins into thermosetting or thermoplastic materials under the irradiation of ultraviolet light. It has the advantages of high precision and high efficiency. However, the current photocuring 3D printing "ink" is mainly petroleum-based materials, which greatly limits its competitiveness in the market. Therefore, using biomass resources with abundant raw material sources and low prices to replace petroleum-based raw materials has become a trend in recent years.

[0003] The global annual production of vegetable oil exceeds 200 million tons, which is a renewable biomass resource with broad application prospects. Palm oil is the world's largest vegetable oil in terms of production, consumption and international trade. Using palm oil as raw material and photocuring 3D printing to produce palm oil-based ion elastomers reduces the use of petroleum-based products and is conducive to the development of a low-carbon economy. Palm oil needs to be synthesized into palm oil fatty acid acrylamide ethyl ester when used, but palm oil fatty acid acrylamide ethyl ester has high viscosity at room temperature and is difficult to react with other reagents or has low reaction efficiency. Therefore, the number of ions produced is small, resulting in the printed objects not being excellent in conductivity, so they need to be improved. Summary of the invention

[0004] The purpose of the present invention is to solve the shortcomings of the prior art and to propose a preparation method of a palm oil-based ion conductive elastomer.

[0005] To achieve the above-mentioned purpose, the present invention adopts the following technical scheme: a preparation method of palm oil-based ion conductive elastomer, wherein the raw material components of the composite material include, by weight: 4 parts of hydroxyethyl acrylate, 0.25-1 parts of acryloyloxyethyl trimethyl ammonium chloride, 5-5.75 parts of palm oil fatty acid acrylamide ethyl ester, 0.005-0.03 parts of graphene oxide and 0.2 parts of photoinitiator.

[0006] Preferably, the molecular structure of the palm oil fatty acid acrylamide ethyl ester is:

[0007] , wherein R1, R2, and R3 are saturated or unsaturated fatty acids; the palm oil fatty acid acrylamide ethyl ester is synthesized from palm oil as a raw material, and the synthesis process is as follows: 150 g of palm oil and 150 mL of tetrahydrofuran are placed in a three-necked flask; then 115 g of N-hydroxyethyl acrylamide, 0.3 g 2, 6-dimethylphenol, and 5 g sodium hydroxide; then, the flask was placed in an oil bath and mechanically stirred (speed 500 r / min) and reacted at 40 °C for 16 h; the reaction product was repeatedly purified 3 to 5 times with saturated brine and purified by rotary evaporation to obtain palm oil fatty acid acrylamide ethyl ester.

[0008] Preferably, the graphene oxide is evenly dispersed in the low eutectic solvent formed by mixing hydroxyethyl acrylate and acryloyloxyethyltrimethylammonium chloride to adjust the resin viscosity, improve the viscosity stability of the resin, and thus improve the printing accuracy. It is evenly dispersed in the palm oil-based resin and can be used as a light absorber to prevent blockage caused by over-curing during 3D printing of hollow pipes. In conjunction with light-curing 3D printing, an ordered microstructure is constructed on the surface of the palm oil-based ion conductive elastomer, which changes the effective contact area of ​​the sensor interface prepared based on the palm oil-based ion conductive elastomer, so that the palm oil-based ion conductive elastomer can be applied to flexible pressure sensors and solve the problem of low sensitivity coefficient of the pressure sensor.

[0009] Preferably, the photoinitiator is phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide.

[0010] Preferably, a specific step for preparing graphene oxide enhanced palm oil-based ion conductive elastomer is as follows: hydroxyethyl acrylate and acryloyloxyethyl trimethyl ammonium chloride are stirred at room temperature for 1 h to prepare the low eutectic solvent, and then graphene oxide is sprinkled in a fully dispersed manner, mechanically stirred at 60°C in ultrasound for 1 h, and palm oil fatty acid acrylamide ethyl ester is added after mixing evenly, and mechanical stirring is continued at 60°C in ultrasound for 3 h. After mixing evenly, the mixture is poured into a photocuring 3D printer to obtain the graphene oxide enhanced palm oil-based ion conductive elastomer, and the ultraviolet light wavelength of the photocuring 3D printer is set to 405 nm.

[0011] Compared with the prior art, the beneficial effects of the present invention are as follows: (1) the low eutectic solvent can provide important functional groups, so that it can form multiple hydrogen bonds with palm oil monomers. The multiple hydrogen bond network structure formed promotes the reaction of various components of the palm oil-based ion conductive elastomer raw material. The rich hydrogen bonds in the multiple hydrogen bond network make the elastomer have high toughness, self-healing, self-repairing and excellent adhesion. The low eutectic solvent provides ions to the blending system so that the palm oil-based ion conductive elastomer has excellent conductivity; (2) graphene oxide is used as a reinforcing material, and 3D printing is used to construct a microstructure on the surface of the elastomer, so that the palm oil-based ion conductive elastomer produces greater deformation when subjected to pressure, increases the compression sensitivity coefficient, and can be applied to flexible pressure sensors; (3) using bio-based palm oil as a raw material and the low eutectic solvent as a solvent, the preparation of raw materials and methods are green and environmentally friendly. BRIEF DESCRIPTION OF THE DRAWINGS

[0012] Figure 1 are the tensile stress-strain curves of five palm oil-based ion-conducting elastomers: 5.25P0.75D4H, 5.5P0.5D4H, 5.75P0.25D4H, 5P1D4H and 6P4H; Figure 2 It is the stretch recovery curve of 5.5P0.5D4H palm oil-based ion-conductive elastomer; Figure 3 are the conductivity of five palm oil-based ion-conductive elastomers: 5.25P0.75D4H, 5.5P0.5D4H, 5.75P0.25D4H, 5P1D4H, and 5P5H; Figure 4 are the sensitivity coefficients of the four palm oil-based ion-conductive elastomers: 5.25P0.75D4H, 5.5P0.5D4H, 5.75P0.25D4H and 5P1D4H; Figure 5 This is a picture of a high-precision palm oil-based ionoelastomer sample; Figure 6 is the conductivity of palm oil-based ion-conducting elastomer recorded for every 0.05% GO increase from 0.05% GO to 0.3% GO ratio; Figure 7 It is the compression loading-unloading cycle curve of 5.5P0.5D4H+0.05%GO; Figure 8 This is a picture of a high-precision graphene oxide-reinforced palm oil-based ionoelastomer sample; Fig. 9 It is the compression sensitivity coefficient of 5.5P0.5D4H+0.05%GO under different pressures and different surface microstructures.

[0013] Meaning of the symbols in the figure: 5.75P.0.25D4H means that the mass ratio of palm oil fatty acid acrylamide ethyl ester, acryloyloxyethyltrimethylammonium chloride and hydroxyethyl acrylate is 5.75:0.25:4; 5.5P0.5D4H means that the mass ratio of palm oil fatty acid acrylamide ethyl ester, acryloyloxyethyltrimethylammonium chloride and hydroxyethyl acrylate is 5.5:0.5:4; 5.25P0.75D4H means that the mass ratio of palm oil fatty acid acrylamide ethyl ester, acryloyloxyethyltrimethylammonium chloride and hydroxyethyl acrylate is 5.25:0.75:4; 5P1D4H means: the mass ratio of palm oil fatty acid acrylamide ethyl ester, acryloyloxyethyltrimethylammonium chloride and hydroxyethyl acrylate is 5:1:4; 6P4H means: the mass ratio of palm oil fatty acid acrylamide ethyl ester and hydroxyethyl ester is 6:4; 5P5H means: the mass ratio of palm oil fatty acid ethyl acrylamide and hydroxyethyl acrylate is 5:5; GO stands for: graphene oxide. DETAILED DESCRIPTION

[0014] In order to provide a further understanding of the purpose, structure, features, and functions of the present invention, the following detailed description is given in conjunction with the embodiments.

[0015] Raw materials: Palm oil (PO) (melting point: 18°C; acid value: 0.16 mg KOH / g) was purchased from Shanghai Dingfen Chemical Technology Co., Ltd., China; N -(2-Hydroxyethyl)acrylamide (>98%), 2, 6-dimethylphenol (>99%), sodium chloride (≥99.5%), dichloromethane (≥99.5%), sodium hydroxide (≥96%), hydroxyethyl acrylate (96%, containing 200-600 ppm MEHQ stabilizer), acryloyloxyethyl trimethylammonium chloride (80 wt%, containing 300 ppm MEHQ stabilizer), phenyl bis(2, 4, 6-trimethylbenzoyl-phosphine oxide (photoinitiator TPO819, >97%) were purchased from Aladdin (Shanghai) Reagent Co., Ltd.; tetrahydrofuran (≥99.5%) was purchased from Sinopharm Chemical Reagent Co., Ltd.

[0016] The synthesis process of palm oil fatty acid acrylamide ethyl ester: 150 g palm oil and 150 mL tetrahydrofuran were placed in a three-necked flask; then 115 g N -hydroxyethyl acrylamide, 0.3 g 2, 6-dimethylphenol, and 5 g sodium hydroxide; then, the flask was placed in an oil bath and mechanically stirred (speed 500 r / min) and reacted at 40 °C for 16 h; the reaction product was repeatedly purified 3 to 5 times with saturated brine and then purified by rotary evaporation to obtain palm oil fatty acid acrylamide ethyl ester. Example

[0017] 3D printing method of palm oil-based ion conductive elastomer: 12 g of hydroxyethyl acrylate and 0.75 g of acryloyloxyethyl trimethyl ammonium chloride are mixed, and magnetic stirring is performed at room temperature for 1 h to obtain a low eutectic solvent; 17.25 g of palm oil fatty acid acrylamide ethyl ester and 0.6 g of photoinitiator are added to the stirred low eutectic solvent, and magnetic stirring is performed at 40 ° C for 1 h. After mixing evenly, the mixture is put into the material tank of a 3D printer and printed under ultraviolet light with a wavelength of 405 nm. The curing time of each layer is set to 15 s.

[0018] Among them, the mass ratio of palm oil fatty acid acrylamide ethyl ester, acryloyloxyethyltrimethylammonium chloride and hydroxyethyl acrylate is 5.75:0.25:4. Example

[0019] 3D printing method of palm oil-based ion conductive elastomer: 12 g of hydroxyethyl acrylate and 1.5 g of acryloyloxyethyl trimethyl ammonium chloride are mixed, and magnetic stirring is performed at room temperature for 1 h to obtain a low eutectic solvent; 16.5 g of palm oil fatty acid acrylamide ethyl ester and 0.6 g of photoinitiator are added to the stirred low eutectic solvent, and magnetic stirring is performed at 40 ° C for 1 h. After mixing evenly, the mixture is put into the material tank of a 3D printer and printed under ultraviolet light with a wavelength of 405 nm. The curing time of each layer is set to 15 s.

[0020] Among them, the mass ratio of palm oil fatty acid acrylamide ethyl ester, acryloyloxyethyltrimethylammonium chloride and hydroxyethyl acrylate is 5.5:0.5:4. Example

[0021] 3D printing method of palm oil-based ion conductive elastomer: 12 g of hydroxyethyl acrylate and 2.25 g of acryloyloxyethyl trimethyl ammonium chloride are mixed, and magnetic stirring is performed at room temperature for 1 h to obtain a low eutectic solvent; 15.75 g of palm oil fatty acid acrylamide ethyl ester and 0.6 g of photoinitiator are added to the stirred low eutectic solvent, and magnetic stirring is performed at 40 ° C for 1 h. After mixing evenly, the mixture is put into the material tank of a 3D printer, and printed under ultraviolet light with a wavelength of 405 nm. The curing time of each layer is set to 15 s.

[0022] Among them, the mass ratio of palm oil fatty acid acrylamide ethyl ester, acryloyloxyethyltrimethylammonium chloride and hydroxyethyl acrylate is 5.25:0.75:4. Example

[0023] 3D printing method for palm oil-based ion conductive elastomer: 12 g of hydroxyethyl acrylate and 3 g of acryloyloxyethyl trimethyl ammonium chloride are mixed, and magnetic stirring is performed at room temperature for 1 h to obtain a low eutectic solvent; 15 g of palm oil fatty acid acrylamide ethyl ester and 0.6 g of photoinitiator are added to the stirred low eutectic solvent, and magnetic stirring is performed at 40 °C for 1 h. After mixing evenly, the mixture is put into the material tank of a 3D printer, and printing is performed under ultraviolet light with a wavelength of 405 nm. The curing time of each layer is set to 15 s.

[0024] Among them, the mass ratio of palm oil fatty acid acrylamide ethyl ester, acryloyloxyethyltrimethylammonium chloride and hydroxyethyl acrylate is 6:1:4. Example

[0025] 3D printing method of palm oil-based ion conductive elastomer: 15 g of hydroxyethyl acrylate, 15 g of palm oil fatty acid ethyl acrylamide and 0.6 g of photoinitiator were mixed, magnetically stirred at 40 °C for 1 h, and then put into the 3D printer material tank after being uniformly mixed. Printing was carried out under ultraviolet light with a wavelength of 405 nm, and the curing time of each layer was set to 15 s.

[0026] Among them, the mass ratio of palm oil fatty acid ethyl acrylamide and hydroxyethyl acrylate is 5:5. Example

[0027] 3D printing method of palm oil-based ion conductive elastomer: 12 g of hydroxyethyl acrylate, 18 g of palm oil fatty acid ethyl acrylamide and 0.6 g of photoinitiator were mixed, magnetically stirred at 40 °C for 1 h, and then put into the 3D printer material tank after being uniformly mixed. Printing was carried out under ultraviolet light with a wavelength of 405 nm, and the curing time of each layer was set to 15 s.

[0028] Among them, the mass ratio of palm oil fatty acid ethyl acrylamide and hydroxyethyl acrylate is 6:4. Example

[0029] 3D printing method of graphene oxide enhanced palm oil-based ion conductive elastomer: 12 g of hydroxyethyl acrylate and 1.5 g of acryloyloxyethyltrimethylammonium chloride were mixed and magnetically stirred at room temperature for 1 h to obtain a low eutectic solvent; 0.015 g of GO was placed in the low eutectic solvent and mechanically stirred in an ultrasonic instrument at 60°C for 1 h, 16.5 g of palm oil fatty acid acrylamide ethyl ester and 0.6 g of photoinitiator were added, and mechanical stirring was continued for 3 h. After mixing evenly, the mixture was placed in the trough of a 3D printer and printed under ultraviolet light with a wavelength of 405 nm. The curing time of each layer was set to 15 s.

[0030] Among them, the mass ratio of palm oil fatty acid acrylamide ethyl ester, acryloyloxyethyltrimethylammonium chloride and hydroxyethyl acrylate is 5.5:0.5:4; the mass of graphene oxide accounts for 0.05% of the total mass of the resin. Example

[0031] 3D printing method of graphene oxide enhanced palm oil-based ion conductive elastomer: 12 g of hydroxyethyl acrylate and 1.5 g of acryloyloxyethyltrimethylammonium chloride were mixed and magnetically stirred at room temperature for 1 h to obtain a low eutectic solvent; 0.03 g of GO was placed in the low eutectic solvent and mechanically stirred in an ultrasonic instrument at 60°C for 1 h, 16.5 g of palm oil fatty acid acrylamide ethyl ester and 0.6 g of photoinitiator were added, and mechanical stirring was continued for 3 h. After mixing evenly, the mixture was placed in the trough of a 3D printer and printed under ultraviolet light with a wavelength of 405 nm. The curing time of each layer was set to 15 s.

[0032] Among them, the mass ratio of palm oil fatty acid acrylamide ethyl ester, acryloyloxyethyltrimethylammonium chloride and hydroxyethyl acrylate is 5.5:0.5:4; the mass of graphene oxide accounts for 0.1% of the total mass of the resin. Example

[0033] 3D printing method of graphene oxide enhanced palm oil-based ion conductive elastomer: 12 g of hydroxyethyl acrylate and 1.5 g of acryloyloxyethyltrimethylammonium chloride were mixed and magnetically stirred at room temperature for 1 h to obtain a low eutectic solvent; 0.045 g of GO was placed in the low eutectic solvent and mechanically stirred in an ultrasonic instrument at 60°C for 1 h, 16.5 g of palm oil fatty acid acrylamide ethyl ester and 0.6 g of photoinitiator were added, and mechanical stirring was continued for 3 h. After mixing evenly, the mixture was placed in the trough of a 3D printer and printed under ultraviolet light with a wavelength of 405 nm. The curing time of each layer was set to 15 s.

[0034] Among them, the mass ratio of palm oil fatty acid acrylamide ethyl ester, acryloyloxyethyltrimethylammonium chloride and hydroxyethyl acrylate is 5.5:0.5:4; the mass of graphene oxide accounts for 0.15% of the total mass of the resin. Example

[0035] 3D printing method of graphene oxide enhanced palm oil-based ion conductive elastomer: 12 g of hydroxyethyl acrylate and 1.5 g of acryloyloxyethyl trimethylammonium chloride were mixed and magnetically stirred at room temperature for 1 h to obtain a low eutectic solvent; 0.06 g of GO was placed in the low eutectic solvent and mechanically stirred in an ultrasonic instrument at 60°C for 1 h, 16.5 g of palm oil fatty acid acrylamide ethyl ester and 0.6 g of photoinitiator were added, and mechanical stirring was continued for 3 h. After mixing evenly, the mixture was placed in the trough of a 3D printer and printed under ultraviolet light with a wavelength of 405 nm. The curing time of each layer was set to 15 s.

[0036] Among them, the mass ratio of palm oil fatty acid acrylamide ethyl ester, acryloyloxyethyltrimethylammonium chloride and hydroxyethyl acrylate is 5.5:0.5:4; the mass of graphene oxide accounts for 0.2% of the total mass of the resin. Example

[0037] 3D printing method of graphene oxide enhanced palm oil-based ion conductive elastomer: 12 g of hydroxyethyl acrylate and 1.5 g of acryloyloxyethyltrimethylammonium chloride were mixed and magnetically stirred at room temperature for 1 h to obtain a low eutectic solvent; 0.075 g of GO was placed in the low eutectic solvent and mechanically stirred in an ultrasonic instrument at 60°C for 1 h, 16.5 g of palm oil fatty acid acrylamide ethyl ester and 0.6 g of photoinitiator were added, and mechanical stirring was continued for 3 h. After mixing evenly, the mixture was placed in the trough of a 3D printer and printed under ultraviolet light with a wavelength of 405 nm. The curing time of each layer was set to 15 s.

[0038] Among them, the mass ratio of palm oil fatty acid acrylamide ethyl ester, acryloyloxyethyltrimethylammonium chloride and hydroxyethyl acrylate is 5.5:0.5:4; the mass of graphene oxide accounts for 0.25% of the total mass of the resin. Example

[0039] 3D printing method of graphene oxide enhanced palm oil-based ion conductive elastomer: 12 g of hydroxyethyl acrylate and 1.5 g of acryloyloxyethyltrimethylammonium chloride were mixed and magnetically stirred at room temperature for 1 h to obtain a low eutectic solvent; 0.09 g of GO was placed in the low eutectic solvent and mechanically stirred in an ultrasonic instrument at 60°C for 1 h, 16.5 g of palm oil fatty acid acrylamide ethyl ester and 0.6 g of photoinitiator were added, and mechanical stirring was continued for 3 h. After mixing evenly, the mixture was placed in the trough of a 3D printer and printed under ultraviolet light with a wavelength of 405 nm. The curing time of each layer was set to 15 s.

[0040] Among them, the mass ratio of palm oil fatty acid acrylamide ethyl ester, acryloyloxyethyltrimethylammonium chloride and hydroxyethyl acrylate is 5.5:0.5:4; the mass of graphene oxide accounts for 0.3% of the total mass of the resin.

[0041] Palm oil-based ion conductive elastomer mechanical properties test: Composite materials and light-curing 3D printers were used to print dumbbell-shaped samples (specifications: 75 mm long, 12 mm wide; 25 mm long in the middle, 4 mm wide, and 1 mm thick) for tensile performance testing; the tensile performance test was carried out in accordance with GB / T 17037.2‒2020. The tensile performance test was carried out on a microcomputer-controlled electronic universal testing machine at a speed of 50 mm / min.

[0042] Dumbbell-shaped palm oil-based ion conductive elastomer samples were subjected to cyclic tensile tests (loading and unloading) at a rate of 50 mm / min at room temperature; in each cycle, the sample was stretched to 300% strain, and there was no relaxation time between the 1st to the 4th cycle; after the 4th cycle, the specimen was relaxed at room temperature for 2 h before being stretched for the 5th time.

[0043] Electrical properties test of palm oil-based ion conductive elastomer: The resistance of the elastomer was tested by a four-probe method using an LCR digital bridge, and the conductivity was calculated based on the relationship between the conductivity and the resistance, area, and length of the measured palm oil-based ion-conductive elastomer.

[0044] The palm oil-based ion conductive elastomer was stretched by 50%, 100%, 150% and 200% at a speed of 50 mm / min using a microcomputer-controlled electronic universal testing machine. The signal changes were recorded using an LCR digital bridge. The sensitivity coefficient was calculated based on the slope between the resistance change rate and the strain.

[0045] Palm oil-based ion conductive elastomers with different surface microstructures were printed using a 3D printer. Different pressures of 3.27 kPa, 8.18 kPa and 16.25 kPa were applied on the surfaces of different microstructures, and their signals were recorded using an LCR digital bridge. The sensitivity coefficient was calculated based on the slope between the resistance change rate and pressure.

[0046] Depend on Figure 1 It can be seen that the tensile stresses of 5.25P0.75D4H, 5.5P0.5D4H, 5.75P0.25D4H and 5P1D4H are 0.74 MPa, 0.66 MPa, 0.72 MPa and 0.53 MPa, respectively, indicating that the tensile stress of the palm oil-based ion conductive elastomer is significantly reduced after the addition of acryloyloxyethyltrimethylammonium chloride; the tensile strains are 605%, 717%, 532% and 479%, respectively, indicating that the tensile strain of the palm oil-based ion conductive elastomer shows a trend of first increasing and then decreasing with the increase of acryloyloxyethyltrimethylammonium chloride.

[0047] Depend on Figure 2 It can be seen that 5.5P0.5D4H palm oil-based ion conductive elastomer has good recovery. The specific data are as follows: the tensile strain is 300%, and after 5 stretching cycles, the tensile stress after recovery for 2 hours is 0.34 MPa, which is 87% of the initial strength; the tensile toughness recovers to 0.27 MJ / m³, which is 79% of the initial toughness.

[0048] Depend on Figure 3 It can be seen that the printed palm oil-based ion conductive elastomer has excellent conductivity. With the increase of the content of acryloyloxyethyl trimethyl ammonium chloride, the conductivity of the palm oil-based ion conductive elastomer increases, and the maximum conductivity is 6.6×10 −3 s / m.

[0049] Depend on Figure 4It can be seen that the sensitivity coefficients of the printed four palm oil-based ion conductive elastomers, 5.25P0.75D4H, 5.5P0.5D4H, 5.75P0.25D4H and 5P1D4H, are all greater than 1, which can amplify the input signal and generate a larger output signal. The palm oil-based ion conductive elastomer 5.5P0.5D4H has the largest sensitivity coefficient of 2.98.

[0050] Depend on Figure 5 and Figure 8 It can be seen that the optical photographs show that the printed palm oil-based ion conductive elastomer has high precision, and the details of the palm oil-based ion conductive elastomer sample are also fully displayed.

[0051] Depend on Figure 6 It can be seen that the conductivity of the printed GO / palm oil-based ion conductive elastomer decreases with the increase of GO.

[0052] Depend on Figure 7 It can be seen that GO has a greater influence on palm oil-based ion conductive elastomers. After adding GO, the elongation at break is significantly reduced.

[0053] As shown in Table 1, the introduction of microstructures on the surface of GO / palm oil-based ion conductive elastomer improves the compression sensitivity coefficient. The pyramid has the largest sensitivity coefficient, which is 22.93 kPa. −1 , followed by cylinder and cube.

[0054] The present invention has been described by the above-mentioned relevant embodiments, however, the above-mentioned embodiments are only examples for implementing the present invention. It must be pointed out that the disclosed embodiments do not limit the scope of the present invention. On the contrary, changes and modifications made without departing from the spirit and scope of the present invention are all within the scope of patent protection of the present invention.

Claims

1. A method for preparing a palm oil-based ion-conductive elastomer, characterized in that: The raw material components of the composite material include: hydroxyethyl acrylate, acryloyloxyethyl trimethyl ammonium chloride, palm oil fatty acid acrylamide ethyl ester, graphene oxide and a photoinitiator.

2. The method for preparing a palm oil-based ion conductive elastomer according to claim 1, characterized in that: The molecular structural formula of the palm oil fatty acid acrylamide ethyl ester is: , wherein R1, R2, and R3 are saturated or unsaturated fatty acids; the palm oil fatty acid acrylamide ethyl ester is synthesized from palm oil as a raw material, and the synthesis process is as follows: palm oil and tetrahydrofuran are placed in a three-necked flask; then, N -hydroxyethyl acrylamide, 2, 6-dimethylphenol, and sodium hydroxide; then, the flask is placed in an oil bath and mechanically stirred for a long time; the reaction product is repeatedly purified by saturated brine and rotary evaporation to obtain palm oil fatty acid acrylamide ethyl ester.

3. The method for preparing a palm oil-based ion conductive elastomer according to claim 1, characterized in that: The graphene oxide is evenly dispersed in the low eutectic solvent formed by mixing hydroxyethyl acrylate and acryloyloxyethyltrimethylammonium chloride, and is combined with photocuring 3D printing to construct an ordered microstructure on the surface of the palm oil-based ion conductive elastomer, so that the effective contact area of ​​the sensor interface prepared based on the palm oil-based ion conductive elastomer changes.

4. The method for preparing a palm oil-based ion-conductive elastomer according to claim 1, characterized in that: The photoinitiator is phenyl bis (2,4,6-trimethylbenzoyl) phosphine oxide.

5. A method for preparing a palm oil-based ion-conductive elastomer reinforced with graphene oxide as claimed in claim 1, characterized in that: The specific steps are as follows: hydroxyethyl acrylate and acryloyloxyethyl trimethyl ammonium chloride are stirred at room temperature to prepare the low eutectic solvent, and then graphene oxide is sprinkled in a fully dispersed manner, mechanically stirred in ultrasound, and palm oil fatty acid acrylamide ethyl ester is added after mixing evenly, and mechanical stirring is continued under ultrasound, and after mixing evenly, the mixture is poured into a photocuring 3D printer to obtain the graphene oxide enhanced palm oil-based ion conductive elastomer.

Citation Information

Patent Citations

  • Palm oil-based thermoplastic elastomer for digital light processing 3D printing

    CN111848867A

  • Bio-based acrylic monomers and polymers thereof

    US20170226050A1

Cited By

  • Photo-curing 3D printing carbon-containing conductive porous material as well as preparation method and application thereof

    CN120665428A